Penggunaan Metode Eksperimen untuk meningkatkan Hasil Belajar Siswa tentang Cahaya di Kelas V SDN 07 Silaut Kecamatan Silaut - Rukinem Rukinem (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2018)
This study originated from the fact in the School that learning is often dominated by teachers so that student learning outcomes about Light material are not as expected. The purpose of this study was to improve the learning outcomes of Light in class V SDN 07 Silaut. This type of research is classroom action research with an experimental method. This study uses a qualitative and quantitative approach which is carried out in two collaborative cycles between researchers and teachers. Research subjects were teachers and grade V elementary school students. The results showed that using experimental methods can improve the learning outcomes of grade V students.